Synthesizing Tradition: Physical Modeling and Composition with the Colombian Gaita - Rincón, Juan Felipe Vásquez; Rossetti, Danilo (Anais do Simpósio Brasileiro de Computação Musical, 2025)
This article focuses on the physical modeling of the Colombian gaita using waveguide synthesis techniques. Based on an acoustic analysis of the instrument, the gaitacol∼ object was developed in the MAX/MSP environment to simulate its sound in real time. The resulting synthesis was integrated into the composition Entre tanto y tanto, un caminar continuo, where the dialogue between the acoustic and digital versions of the gaita explores the convergence of traditional sound and technological processes. This work contributes to the field of computer music by applying physical modeling to a non-Western instrument and proposing creative frameworks for its integration into contemporary composition.